Secrets of the Greatest Snow on Earth : Weather, Climate Change, and Finding Deep Powder in Utah's Wasatch Mountains and around the World - Steenburgh, Jim (Book collections on Project MUSE., 2014)
Utah has long claimed to have the greatest snow on Earth-the state itself has even trademarked the phrase. In Secrets of the Greatest Snow on Earth, Jim Steenburgh investigates Wasatch weather, exposing the myths, explaining the reality, and revealing how and why Utah's powder lives up to its reputation. Steenburgh also examines ski and snowboard regions beyond Utah, making this book a meteorological guide to mountain weather and snow climates around the world. Chapters explore mountain weather, avalanches and snow safety, historical accounts of weather events and snow conditions, and the basics of climate and weather forecasting. Steenburgh explains what creates the best snow for skiing and snowboarding in accurate and accessible language and illustrates his points with 150 color photographs, making Secrets of the Greatest Snow on Earth a helpful tool for planning vacations and staying safe during mountain adventures. Snowriders, weather enthusiasts, meteorologists, students of snow science, and anyone who dreams of deep powder and bluebird skies will want to get their gloves on Secrets of the Greatest Snow on Earth. Watch Book Trailer!(Special thanks to Ski Utah).